Music and ceremony at the court of Charles V : the Capilla Flamenca and the art of political promotion - Ferer, Mary Tiffany (Studies in medieval and Renaissance music, 2012)
The presentation of Charles V as universal monarch, defender of the faith, magnanimous peacemaker, and reborn Roman Emperor became the mission of artists, poets, and chroniclers, who shaped contemporary perceptions of him and engaged in his political promotion. Music was equally essential to the making of his image, as this book shows. It reconstructs musical life at his court, by examining the compositions which emanated from it, the ordinances prescribing its rituals and ceremonies, and his prestigious chapel, which reflected his power and influence.